2013
DOI: 10.1136/gutjnl-2013-305092
|View full text |Cite
|
Sign up to set email alerts
|

Obesity acceleratesHelicobacter felis-induced gastric carcinogenesis by enhancing immature myeloid cell trafficking and TH17 response

Abstract: Objective To investigate the role of obesity-associated inflammation and immune modulation in gastric carcinogenesis during Helicobacter-induced chronic gastric inflammation. Design C57BL/6 male mice were infected with H felis and placed on a high-fat diet (45% calories from fat). Study animals were analysed for gastric and adipose pathology, inflammatory markers in serum, stomach and adipose tissue, and immune responses in blood, spleen, stomach and adipose tissue. Results H felis-induced gastric carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…However, in addition to neutrophils other cells including dendritic cells, and myeloid suppressor monocytes also express Gr1[63;65;66]. Recent studies have shown that myeloid–derived suppressor cells (MDSCs) contribute to H. pylori -related inflammation and carcinogenesis [6769], as well as modulation of IFN-γ responses [70]. To determine whether the levels of Gr1 expression in the gastric mucosa of wild type and CD44−/− infected mice differed, we conducted IHC for Gr1 and found that WT mice infected with H. pylori had a high number of Gr1+ cells infiltrating their gastric mucosa (>30 per high power field) both in the corpus and in the antrum (Figure 6A and B, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…However, in addition to neutrophils other cells including dendritic cells, and myeloid suppressor monocytes also express Gr1[63;65;66]. Recent studies have shown that myeloid–derived suppressor cells (MDSCs) contribute to H. pylori -related inflammation and carcinogenesis [6769], as well as modulation of IFN-γ responses [70]. To determine whether the levels of Gr1 expression in the gastric mucosa of wild type and CD44−/− infected mice differed, we conducted IHC for Gr1 and found that WT mice infected with H. pylori had a high number of Gr1+ cells infiltrating their gastric mucosa (>30 per high power field) both in the corpus and in the antrum (Figure 6A and B, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…reuteri ATCC 6475 administration reduced the levels of this cytokine, presumably by restoring Foxp3+ Treg/Th17 balance [ 37 ]. In our study, the increased serum leptin concentration could also contribute to the enhanced Th17 response, suggested by the increased serum IL-17A levels in obese mice [ 38 ]. However, this effect could not be attributed to cytokines involved in Th17 cell differentiation and maintenance, such as IL-6 and IL-1β [ 38 ], because their concentrations were not significantly increased in serum of our obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of gastric leptin in diet-induced obesity-associated gastric atrophy has not previously been investigated, although the elevation of serum leptin contributes to tumorigenesis in the stomach of obese mice infected with H. felis [ 66 ]. In the current study, we showed rapid (1 week) mucosal morphological changes in the gastric cardia (Fig.…”
Section: Discussionmentioning
confidence: 99%